Dampak Inflasi Dan Kurs Terhadap Biaya Produksi - Sarwo Edy Handoyo; Elvi (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2010)
This research was conducted to determine whether there is a significant relationship between inflation and exchange rate against the company's production costs. The data used are secondary data where the dependent variable data obtained from the cost of production period January 2006 - December 2007, while for the independent variables obtained from inflation and exchange rate for the period January 2006 - December 2007. Methods of data collection are done by using observations. To find out the results of this study, the classical assumption testing and testing hypotheses of multiple regression models with the help of the computer program SPSS version 14.00. Based on the analysis and discussion that has been done, the conclusion is that there is a significant relationship between inflation and exchange rate against the company's production costs for the period January 2006 to December 2007.